COUNTRY FOCUS Micro, Small and Medium Enterprises in Kenya: Current State, Opportunities and Challenges - Bitange Ndemo; Ben Mkalama (International Journal of Small and Medium Enterprises and Business Sustainability, 2018)
The Kenyan economy is market-based with a few state-owned infrastructure enterprises and its external trade systems are largely liberalized. It is the largest economy in the East and Central Africa and its capital city, Nairobi is the hub for financial services, communication and transportation services. The economy is well diversified with vibrant manufacturing, mining, agriculture, forestry, fishing and tourism. The country’s gross domestic product (GDP) is estimated to surpass $85 billion in 2018 or the 69th largest economy in the world. Per capita income in 2018 is estimated at $1,790. Statistica (2017) reports that services sector contributed 45% of GDP followed by agriculture at 32% and industry at 17%. The Kenyan economy has enjoyed both periods of great advances and disheartening downturns. Incidences of poverty and unemployment, meagre foreign exchange earnings (exports of primary product mainly - agro-produce) have resulted in unfavourable balance of payment and low per capita income. It is estimated that about 36% (Awiti, et al., 2018) of Kenya’s population live below the poverty line. While, the overall population growth rate has experienced a decline over the last 2 decades, unemployment continues to increase. As a result, lack of productive employment opportunities has led to a fall of real wages in nearly all the sectors of the economy. Further, the population pressure on agricultural land and the associated decline in individual holdings have resulted in low and decreasing productivity. Under the Vision 2030, it is acknowledged that in order to cope with these challenges, the economy will have to consistently grow at between 8-10% (SDGs more than 7%, Vision 2030 more than 10% annually).